2017
DOI: 10.7554/elife.29929
|View full text |Cite
|
Sign up to set email alerts
|

3D visualization of mitochondrial solid-phase calcium stores in whole cells

Abstract: The entry of calcium into mitochondria is central to metabolism, inter-organelle communication, and cell life/death decisions. Long-sought transporters involved in mitochondrial calcium influx and efflux have recently been identified. To obtain a unified picture of mitochondrial calcium utilization, a parallel advance in understanding the forms and quantities of mitochondrial calcium stores is needed. We present here the direct 3D visualization of mitochondrial calcium in intact mammalian cells using cryo-scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 49 publications
7
87
1
Order By: Relevance
“…It has been previously demonstrated that the calcium present in the mitochondrial matrix is buffered in dense calcium-phosphate granules, (Nicholls and Chalmers, 2004). These granules have been found in live cells, after pathological calcium overload, as well as in cells under normal culture conditions, (Wolf et al, 2017). While these granules contain precipitated (non-active) calcium, they can be easily dissolved by mitochondria, when buffering is needed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that the calcium present in the mitochondrial matrix is buffered in dense calcium-phosphate granules, (Nicholls and Chalmers, 2004). These granules have been found in live cells, after pathological calcium overload, as well as in cells under normal culture conditions, (Wolf et al, 2017). While these granules contain precipitated (non-active) calcium, they can be easily dissolved by mitochondria, when buffering is needed.…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we believe the calcium buffering in the form of 434 calcium phosphate granules system becomes relevant. In a separate study, calcium phosphate granule 435 deposits were observed in the matrix near cristae junctions in a variety of different eukaryotic cells under 436 physiological conditions(Wolf et al, 2017). Given the relevance of calcium in bioenergetics, the presence of 437 these calcium deposits may exert some degree of control over mitochondrial signaling and metabolism.…”
mentioning
confidence: 96%
“…As such there is a need to optimize imaging conditions such that SNR, contrast, and resolution are maximized for images collected from thick samples with low electron fluxes. While this has been demonstrated experimentally for resin embedded cells or cryogenic thin sections (16,18), and discussed in theory for liquid and cryogenic samples (19)(20)(21)(22), at the time of this writing the optimal imaging modalities have not been demonstrated experimentally for LC-TEM across equivalent samples on the same instrument. Furthermore, despite demonstrations of hydrated cells imaged with LC-TEM in the literature, images collected with LC-TEM do not consistently show the same level of detail as those imaged with cryo-EM.…”
Section: Introductionmentioning
confidence: 99%